2005
DOI: 10.1038/modpathol.3800380
|View full text |Cite
|
Sign up to set email alerts
|

Superficial vs deep pancreatic parenchymal invasion in the extrahepatic bile duct carcinomas: a significant prognostic factor

Abstract: Pancreatic invasion of the extrahepatic bile duct (EBD) carcinomas is known to have a poor outcome. We hypothesized that EBD carcinoma showing shallow invasion to the pancreas may have a better outcome than the usual deep pancreatic invasion. We divided 87 cases of the distal EBD carcinomas into superficial and deep pancreatic invasion groups according to degrees of the pancreatic invasion. The superficial pancreatic invasion group included cases with tumor abutting the pancreatic lobule or pancreatic parenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Previous studies have shown some prognostic factors, such as resection margin [23], lymph node metastasis [24], and pancreatic parenchymal invasion [25]. Furthermore, some molecules, including KIT [26], epidermal growth factor receptor (EGFR) [27], Caveolin-I [28], and MUC4 [29], were revealed to be prognostic factors of EBD carcinomas, but FAK expression in EBD carcinomas has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown some prognostic factors, such as resection margin [23], lymph node metastasis [24], and pancreatic parenchymal invasion [25]. Furthermore, some molecules, including KIT [26], epidermal growth factor receptor (EGFR) [27], Caveolin-I [28], and MUC4 [29], were revealed to be prognostic factors of EBD carcinomas, but FAK expression in EBD carcinomas has not been evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In middle and distal cholangiocarcinoma, tumors with deep invasion were associated with poor prognosis compared with those with superficial invasion. 53 Furthermore, the depth of invasion of the primary tumor correlated well with patient survival in middle and distal cholangiocarcinoma, whereas it did not in hilar lesion. 54 Considering these biological characteristics, portal vein invasion in these lesions should be regarded as the depth of invasion of the primary tumor.…”
Section: Portal Vein Involvement In Pancreatic and Biliary Tract Carcmentioning
confidence: 97%
“…For example, Saito et al [23] reported the identification of 4 independent factors -a serum CEA level >7.0 ng/mL, Alb level <3.5 g/dL, CRP level >0.5 mg/dL, and PLR >150 -that could be measured preoperatively and used to predict the prognosis of patients with perihilar cholangiocarcinoma. Table 4 summarizes recent reports that identified lymph node metastasis, stage, GPS, and tumor differentiation as prognostic factors of distal cholangiocarcinoma [8,[15][16][17][18][19][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%